[quotation] On forests and futures - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
On forests and futures: 'Our entire vision could be summed up in the tree nurseries we are using to replenish our flora we are planting the traditions of the third millennium' Rija Rajohnson, Malagasy Minister of Forestry, 1999